Students' Difficulties in Constructing Argumentative Texts: A Genre-Based Analysis at SMPN 27 Medan - Stefani Angelica Sinambela; Mira Mailani; Murni Murni; Nayla Firzanah (CV Edu Tech Jaya, 2026)
Writing argumentative texts is one of the essential skills that students need to develop in English language learning. However, many students still experience difficulties in constructing argumentative texts effectively. This study aimed to identify the difficulties encountered by eighth-grade students of SMP Negeri 27 Medan in constructing argumentative texts and to analyze the generic structures and language features used in their writing. This study employed a descriptive qualitative research design. The participants consisted of 24 eighth-grade students of SMP Negeri 27 Medan. The data were collected through writing tasks and documentation. The students were asked to write argumentative texts based on several assigned topics. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014), including data condensation, data display, and conclusion drawing. The analysis was conducted based on Genre-Based Analysis proposed by Gerot and Wignell (1994), focusing on generic structures and language features of argumentative texts. The findings revealed that argument development was the most significant difficulty experienced by students, with 75% producing underdeveloped arguments. Grammatical errors were found in 71% of the texts, while 67% of the students demonstrated limited vocabulary usage and 58% showed inappropriate use of logical connectors. Despite these difficulties, all students were able to construct thesis statements and conclusions appropriately. The study concludes that students possess a basic understanding of argumentative text structure but still require greater support in developing arguments, improving grammatical accuracy, enriching vocabulary, and applying cohesive devices effectively. These findings highlight the importance of genre-based instruction in improving students’ argumentative writing competence.